2016
DOI: 10.1177/0333102416652092
|View full text |Cite
|
Sign up to set email alerts
|

OnabotulinumtoxinA improves quality of life and reduces impact of chronic migraine over one year of treatment: Pooled results from the PREEMPT randomized clinical trial program

Abstract: BackgroundChronic migraine (CM) is associated with high impact and reduced health-related quality of life (HRQoL).MethodsPatients with CM from PREEMPT (Phase 3 REsearch Evaluating Migraine Prophylaxis Therapy) were randomized (1:1) to receive onabotulinumtoxinA or placebo for two 12-week cycles in the double-blind (DB) phase, followed by three 12-week cycles of open-label (OL) onabotulinumtoxinA (onabotulinumtoxinA/onabotulinumtoxinA (O/O) and placebo/onabotulinumtoxinA (P/O) groups, respectively). HRQoL endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 28 publications
(72 reference statements)
7
65
0
1
Order By: Relevance
“…Both CM and HFEM are associated with high disability, impact and reduced quality of life. In our cohort, disability was assessed at each time point using the HIT-6 and MIDAS scales, showing a significant reduction in MIDAS score from baseline to month 24 in CM, as had been previously demonstrated [29]. Our data also reproduce the long-term benefit seen in other cohorts [25,26].…”
Section: Discussionsupporting
confidence: 84%
“…Both CM and HFEM are associated with high disability, impact and reduced quality of life. In our cohort, disability was assessed at each time point using the HIT-6 and MIDAS scales, showing a significant reduction in MIDAS score from baseline to month 24 in CM, as had been previously demonstrated [29]. Our data also reproduce the long-term benefit seen in other cohorts [25,26].…”
Section: Discussionsupporting
confidence: 84%
“…Subsequent exploratory and confirmatory factor analysis and patient interviews reduced the number of items to 14, which revealed and confirmed 3 meaningful domains measured by the MSQ: Role Function‐Restrictive (RFR), Role Function‐Preventive (RFP), and Emotional Function (EF) . Overall, the rigorous development and strong psychometric properties of the MSQ have resulted in extensive research, including numerous clinical trials spanning more than 2 decades . The MSQ is recommended as a core instrument for headache studies by the National Institutes of Health…”
Section: Introductionmentioning
confidence: 99%
“…This instrument is widely used, has been shown to correlate highly with the MSQ and other migraine measures of disability, and is a reliable and valid tool for discriminating headache impact across both episodic and chronic migraine . Evidence from migraine prevention trials has demonstrated that HIT‐6 is sensitive to treatment effects …”
Section: Introductionmentioning
confidence: 99%
“…In the United States, chronic migraine prevalence is nearly 1% and results in enormous impact on headache-related disability, including higher Migraine Disability Assessment Test (MIDAS), reduced health-related quality of life (HRQoL), increased depression and anxiety (PHQ-4 and GAD-7 respectively), compared to episodic migraine [16]. Chronic migraine has also been shown to result in greater economic burden and health care resource utilization [1, 3, 79]. Annually, the total economic cost of chronic migraine is over three time that of episodic migraine, when consider direct medical costs and loss from decreased productivity [8].…”
Section: Introductionmentioning
confidence: 99%